PHARMACOLOGICAL EVALUATION OF METHANOLIC EXTRACT OF TRICHODESMA INDICUM (LINN)R.Br. - Azhaguraman, Chidambaram; Aruna, Ajithadas (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The methanolic extract of the whole plant of Trichodesma indicum Linn R.Br. was screened for its in-vitro antioxidant, anti bacterial and wound healing activity. The antioxidant activity was screened by Nitric oxide scavenging and reducing power assay method. The methanolic extract showed good antioxidant potential. The antibacterial and wound healing potency of the extract was screened by preparing an ointment formulation using simple ointment base. It has good antibacterial activity against the tested organisms when compared with control base. It has complete rate of contraction (closure 99.63%) when compared with standard Neosporin treated and control base treated group when studies for wound healing potency. Keywords: Trichodesma indicum Linn R.Br, Antioxidant, Wound healing, Antibacterial activity.